The COronal Diagnostic EXperiment (CODEX): pre-flight polarimetric characterization - Casti, Marta; Newmark, Jeffrey S.; Kim, Yeon-Han; Capobianco, Gerardo; Haudemand, Hervé; Song, Donguk; Park, Sung-Hong; Bong, Su-Chan; Cho, Kyungsuk; Choi, Seonghwan; Gong, Qian; Baek, Ji-Hye; et al. (Frontiers in Astronomy and Space Sciences, 2026)
The COronal Diagnostic EXperiment (CODEX) is an externally occulted solar coronagraph designed to observe the linearly polarized K-corona to simultaneously measure the electron density, kinetic temperature, and speed. The objective of this work is to provide a detailed description of the characterization of the CODEX coronagraph from a polarimetric point of view. The final goal is to minimize the uncertainties associated with the outcome of the observation data analysis by removing the contributions of artifacts introduced by the optical elements within the instrument. This aspect is particularly critical for the CODEX coronagraph, since it is provided with a polarization image sensor, the IMX253MZR manufactured by Sony, that spatially modulates the incoming light beam. Moreover, the optical path of the instrument is composed of several elements including two fold-mirrors positioned at 90°, a system that is notoriously a source of polarization aberrations. The methodology used consists of introducing a light beam with a known polarization state into the instrument and measuring its response. Repeated measurements for different states of polarization of the incoming beam allow one to derive the matrix that connects the Stokes vector of the input light to the intensity measured by the detector. The outcome of this analysis is represented by this matrix, which will be used to derive the Stokes vector of the coronal light from the data acquired by CODEX during its mission and that takes into account the instrumental effects. This will minimize the instrumental effects on coronal polarization that occur if one simply derives the Stokes vector by combining the observed polarized images.